The short-term impacts of cooperative, connected, and automated mobility on passenger transport - Rajae Haourari; Amna Chaudhry; Hua Sha; Gerard Richter; Mohit Singh; Evita Papazikou; Hitesh Boghani; Julia Roussou; Bin Hu; Pete Thomas; Mohammed Quddus; Andrew Morris (2021)
The aim of the LEVITATE project is to prepare a new impact assessment framework to enable policymakers to manage the introduction of cooperative, connected, and automated transport systems, maximise the benefits and utilise the technologies to achieve societal objectives. As part of this work, the LEVITATE project seeks to forecast societal level impacts of cooperative, connected, and automated mobility (CCAM). The aim of this report is to provide an analysis of the short-term impacts, described in Deliverable 3.1 (Elvik et al.,2019), of different passenger car transport sub-use cases (policy interventions). The short-term impacts analysed include travel time, vehicle operating cost, and access to travel. Based on several discussions with the stakeholder reference group (SRG) including city officials and industry professionals, a list of key interventions, termed sub-use cases (SUCs), were selected to be tested through different applicable methods. These include road use pricing (rup), provision of dedicated lanes on urban highways, parking price policies, parking space regulations, automated ride sharing, and green light optimal speed advisory (GLOSA). For assessing the travel time impact, mesoscopic and microscopic simulation as well as Delphi method have been used. The Delphi method was also used to estimate impacts on vehicle operating cost and access to travel. Road Use Pricing was modelled through mesoscopic simulation using the full-scale city-level model of Vienna. All other sub-use cases were analysed through microscopic simulation method using Manchester network for Dedicated Lanes, Automated Ride Sharing and GLOSA, Leicester network for Parking Space Regulations, and Santander model for testing Parking Price Policies. [...]